PENETRASI BUDAYA YAHUDI DALAM AJARAN ISLAM - Turmudzi, Ahmad (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2013)
AbstractPenetration and acculturation cause problems for the adherents of certain religions. It was experienced by Muslims when the Jewish culture influenced the heart teachings of Islam such as the interpretation of the Prophet of the Qur’an and Hadith. Fairy tales and the information obtained from Jewish culture had scattered in the works of tafsir al-Qur’an. While in the Hadith of the Prophet, the influence of Jewish culture was transformed into false hadiths (mawdlu’at) that contained stories that are misleading superstition. This article examines the influence of Jews (Israiliyat) in the interpretation of the Koran. Some of the questions that the author has answered in this paper are how the history of Jewish had influenced the religious teachings of Islam; what the dangers arise from the existence of such influences, and what efforts Muslim scholars have tackled the influences of these.